Pencatat Keuangan: Pengembangan Aplikasi Futter untuk Mencatat dan Mengelola Transaksi Keuangan - Munawir Sajali Harahap; Richi Andrianto; Dermilan Dermilan; Dewi Elok; Citra Khoiriah; Babang Andika (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This journal discusses the development of a financial note-taking application using Flutter, a development framework that is well known in the creation of cross-platform applications. The purpose of this application is to provide support for users in recording and managing their personal finances in an easy, efficient, and interactive way. This article outlines the steps taken in the development of the application, starting from analyzing user needs to implementing and testing the application. Various important features are also described, such as the ability to record income and expenses, monitor budgets, create transaction categories, and generate financial reports.In addition, the journal also discusses the attractive and responsive user interface generated by Flutter. This framework allows developers to create attractive and responsive interfaces by using widgets and animations provided by Flutter.In the performance evaluation section, the article covers testing the application to measure its performance and responsiveness. The user experience is also evaluated through user studies and feedback collection to ensure that the app meets the user's expectations and needs. In the overall article, the author outlines the benefits and advantages of using Flutter in the development of a financial record app. It is hoped that this application can provide an effective solution for users in organizing and managing their personal finances. Through this journal, readers will gain insight into the process of developing a financial note-taking application using Flutter, as well as a better understanding of the potential and benefits of using Flutter in the development of engaging and responsive cross-platform applications.